PENINGKATAN PROSES BELAJAR DAN HASIL BELAJAR PADA MATA PELAJARAN KESELAMATAN, KESEHATAN KERJA DAN LINGKUNGAN (K3L) DENGAN MODEL PEMBELAJARAN TIPE JIGSAW SISWA KELAS X JURUSAN TEKNIK OTOMOTIF SMK MUHAMMADIYAH GAMPING TAHUN AJARAN 2014/2015 - Arif Darmawan; Tarto Sentono (Jurnal Taman Vokasi, 2015)
The research objectives were to improve (1) the learning process by using the learning model of Jigsaw in learning K3L and (2) the learning outcomes by using learning model of Jigsaw in learning K3L among students of Class X SMK Muhammadiyah Gamping. This study was classroom action research. Data collection techniques used observation and tests. Research instrumentS were a researcher, observation sheets, and test. The data analysis used descriptive analysis. Indicators of learning was increasing the learning and learning outcomes K3L subjects. The results showed that (1) the average percentage of students’ learning in pre cycle was 13.33% with less qualification. The improvement in the first cycle was 54.81% with good qualification. While on the second cycle increased up to 78% with excellent qualifications. (2) Based on data acquisition value of students from pre-action, the first cycle and the second cycle showed that there was improvement of students’ ability. The ability of students’ initial value data obtained through daily tests with an average of 69 to 77.6 in the first cycle with a success rate of value rose by 8.6%. The average value of the second cycle increased from 77.6 in the first cycle to 88.7 in the second cycle with a success rate of value rose by 11%. The increase was due Jigsaw learning method in the second cycle executed better and in accordance with the plan of the cycle I. Thus, it can be concluded that the Jigsaw method can enhance the learning process and learning outcomes K3L.